Analisis Perbandingan Algoritma Bubble Sort, Shell Sort, dan Quick Sort dalam Mengurutkan Baris Angka Acak menggunakan Bahasa Java - Muhammad Luthfi Zulfa; Mikhael Mikhael; Betha Nurina Sari (Jurnal Ilmiah Wahana Pendidikan, 2022)
Sorting data is very useful because sorted data will be easier to check and correct if there are errors. There are various kinds of data sorting algorithms including bubble sort, merge sort, shell sort, radix sort, quicksort, and so on. Sorting data is the best treatment as it will be easier to check and correct if there are errors occurring. In this paper, bubble sort, shell sort, and quick sort are tested to sorting 100 lines of random integer with a value range of 0-100. The result shows that quick sort is the most efficient algorithm because it has the fewest steps, consume less memory, and take a little time while sorting.